Design and analysis of a bi-stable linear force actuator for directly-driven metering pump. (14th September 2018) - Tan, Cao; Li, Bo; Ge, Wenqing; Sun, Binbin
Abstract: As a kind of energy converter, high quality electromagnetic linear actuator is the focus of the research. A new flow regulation method for metering pump is proposed, a novel bi-stable linear force actuator (BLFA) is investigated corresponding to reduce power consumption and enhance drive capability. A coupling model including a loss model, an electromagnetic model and a mechanical model was constructed. The influence rule of the structural parameters on force characteristic was investigated. Through structural parameter design, force versus position characteristic is high-linearity in working area and the minimum threshold value of drive force (start-up force) reaches 139 N without spring mechanism, which effectively reduces the device's volume. Besides, power consumption in holding phase is decreased because of holding force. Moreover, an innovative pulse current excitation mode was adopted to reduce power consumption further. Experimental and simulation results validate the static and dynamic performance of BLFA. The circulating power consumption of prototype is 3.1 J, which does not change with the working frequency and has decreased by 34% compared with the traditional excitation mode. Additionally, the advantage of BLFA's performance was also verified with directly-driven metering pump flow characteristic experiment.